“Hide Our Heads in the Sand”: Environmental information avoidance motives in the United States - Deline, Mary Beth; Rickard, Laura N.; Katreeb, Mary; Adams, Melissa (Frontiers in Communication, 2024)
Information avoidance (IA) is a prevalent information behavior that is used by people to understand and act on environmental issues, yet is understudied in the environmental field, leaving us with an incomplete picture of environmental communication processes and outcomes. Compounding this partial knowledge is a lack of research into people’s own conceptions of IA. Considering these issues together calls for exploratory research into people’s lived experiences of environmental IA. To do so, we focused on a factor that drives behaviors like IA: motives. We investigated environmental IA motives among those living in the US and used the pre-theoretical planned risk information avoidance (PRIA) model to compare and contrast our findings. To undertake this work, we developed a short questionnaire; research company YouGov administered the project. They recruited our participants, who were panel members from their US panel, n = 200. We analyzed open-ended data on participants’ IA motives with a framework thematic analysis, identifying seven motives: information credibility and exposure; interpersonal relationship frames; emotional arousal; agency; hazard perceptions; and environmental topics. These findings provide three contributions to environmental IA research. First, three of these motives have been under and/or unexplored in IA studies to date, and we suggest their inclusion in an expanded PRIA model to forward model development. Three other motives indicate boundary conditions associated with environmental issues and IA: scale, timeframe, and referents. Boundary conditions represent how well a theory or model fits into a research context and can sharpen future IA investigations within environmental contexts to increase predictive and explanatory power. Lastly, we also identified the top environmental issues our participants wanted to avoid. Our results provide an initial base to continue developing environmental IA research.